2021
DOI: 10.1016/j.jiph.2021.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Promoting precautionary behavior during the COVID-19 pandemic: Development and validation of a behavior-change messaging campaign

Abstract: Background Designing a health promotion campaign is never an easy task, especially during a pandemic of a highly infectious disease such as COVID-19. In Saudi Arabia, many attempts have been made to raise public awareness about COVID-19 infection and precautionary health measures. However, most of the health information delivered through the national dashboard and the COVID-19 awareness campaigns are generic and do not necessarily make the impact needed to be seen on individuals’ behavior. Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This research provides a proof of concept in terms of how to create a customized awareness health campaign during a pandemic, in this case involving Covid-19 (2020–2022), by creating a map based on the geospatial intelligence technique. The next phase will involve combining the messages created in phase 1 of this project [1] with the visualized map from the second phase (as described in this paper) to send actual messages to users in infected districts and measure the impact of these customized messages. The combination of the two phases can be visualized in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research provides a proof of concept in terms of how to create a customized awareness health campaign during a pandemic, in this case involving Covid-19 (2020–2022), by creating a map based on the geospatial intelligence technique. The next phase will involve combining the messages created in phase 1 of this project [1] with the visualized map from the second phase (as described in this paper) to send actual messages to users in infected districts and measure the impact of these customized messages. The combination of the two phases can be visualized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The first phase of this study aimed to customize the messaging campaign based on the motivation and ability of individuals [1] . This research paper represents the second phase, which aims to add another layer of customization, which involves situational location-aware segments to separately target the local citizens of each district.…”
Section: Introductionmentioning
confidence: 99%
“…This factor has drawn researchers’ attention recently in public health related contexts. Alrige et al (2021) reckoned that anticipation is the most critical motivator in a precautionary health behavior study during the COVID-19 pandemic, while Agha (2022) reported a behavior study on COVID-19 vaccination. The researchers discovered that people with a higher anticipation are more likely to adopt a behavior.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The FBM proposes that after experiencing the trigger, people with sufficiently high levels of motivation and ability will perform the behaviour. FBM has been widely used in technology design [22,[28][29][30][31][32] and is starting to be applied in social marketing campaigns in public health [33][34][35][36][37][38]. The FBM may be a valuable tool for citizen science projects aiming to change individual behaviour, collecting biodiversity observations in our case [23].…”
Section: Selection Of the Theoretical Frameworkmentioning
confidence: 99%